Reproducibility of the alcoholic beverages and illicit drug modules of the 2015 National Survey of School Health - Almeida, Camila Souza de; Andrade, Silmara Nunes; Abreu, Mery Natali Silva; Malta, Deborah Carvalho; Lana, Francisco Carlos Félix (Revista da Escola de Enfermagem da USP, 2020)
Objective: To evaluate the reproducibility of the modules of use of alcoholic beverages and illicit drugs of the 2015 National Survey of School Health. Method: Cross-sectional epidemiological study aimed at evaluating the reproducibility of collection instruments, conducted in the city of Divinópolis, Minas Gerais. The sample consisted of students attending the 9th grade of public and private primary schools in 2017. The reproducibility of the modules of use of alcohol and illicit drugs was applied to the sample and the retest occurred within 15 to 20 days with the same students. In the analysis of the test-retest agreement, the Kappa coefficient was used to analyze the nominal categorical variables; Kappa with linear weighting, in the analysis of ordinal categorical variables; and Intraclass Correlation Coefficient in the analysis of numerical variables. Results: Participation of 303 students. The agreement of responses was between satisfactory and moderate and there was no indicator with reasonable or poor agreement. Frequencies were close between the test-retest. Conclusion: The analyzed modules were satisfactory and considered replicable and reliable sources to support Public Policies and programs aimed at adolescents.